Magnetic resonance imaging-guided prostate biopsy—A review of literature - Kulthe Ramesh Seetharam Bhat; Srinivas Samavedi; Marcio Covas Moschovas; Fikret Fatih Onol; Shannon Roof; Travis Rogers; Vipul R. Patel; Ananthakrishnan Sivaraman (Asian Journal of Urology)
Objective: Multiparametric magnetic resonance imaging (MP-MRI) helps to identify lesion of prostate with reasonable accuracy. We aim to describe the various uses of MP-MRI for prostate biopsy comparing different techniques of MP-MRI guided biopsy. Materials and methods: A literature search was performed for “multiparametric MRI”, “MRI fusion biopsy”, “MRI guided biopsy”, “prostate biopsy”, “MRI cognitive biopsy”, “MRI fusion biopsy systems”, “prostate biopsy” and “cost analysis”. The search operation was performed using the operator “OR” and “AND” with the above key words. All relevant systematic reviews, original articles, case series, and case reports were selected for this review. Results: The sensitivity of MRI targeted biopsy (MRI-TB) is between 91%–93%, and the specificity is between 36%–41% in various studies. It also has a high negative predictive value (NPV) of 89%–92% and a positive predictive value (PPV) of 51%–52%. The yield of MRI fusion biopsy (MRI-FB) is similar, if not superior to MR cognitive biopsy. In-bore MRI-TB had better detection rates compared to MR cognitive biopsy, but were similar to MR fusion biopsy. Conclusions: The use of MRI guidance in prostate biopsy is inevitable, subject to availability, cost, and experience. Any one of the three modalities (i.e. MRI cognitive, MRI fusion and MRI in-bore approach) can be used. MRI-FB has a fine balance with regards to accuracy, practicality and affordability.